Climatological characteristics and influencing factors of precipitation from landfalling tropical cyclones in East China - Ye, Longbin; Zhu, Jing; Wang, Zhengshuai; Su, Zhizhong (Frontiers in Earth Science, 2025)
IntroductionThis study investigates the precipitation characteristics of tropical cyclones (TCs) making landfall in East China from 1960 to 2010.MethodsStatistical and factor analysis methodologies were employed, leveraging TC precipitation separation datasets and global reanalysis data.ResultsThe findings indicate that while the annual total precipitation from landfalling TCs is relatively stable, the maximum daily precipitation at individual stations shows a gradual increasing trend. The frequency of TC impacts and the occurrence of TCs inducing extreme precipitation (≥250 mm) follow a distinct "single peak" monthly distribution. Spatially, stations with the highest frequencies of heavy rain are concentrated along the southeastern coast, with intensity weakening inland. Northward-turning TCs after landfall exert the most significant influence on local wind and rainfall. Compared to weak-precipitation TCs, strong-precipitation TCs are characterized by slower movement, higher wind speeds, and lower central pressure.DiscussionThe results further demonstrate that TCs developing under favorable thermal, dynamic, and moisture conditions tend to generate more intense precipitation.